High-performance stainless steels - Kovach, Curtis W. (Nickel Development Institute reference book series, 2000)
This book provides an introduction to high-performance stainless steels for those whose materials needs extend beyond the capabilities of the standard grades, and for those who will benefit from a discussion of the engineering and corrosion performance properties of the high-performance stainless steels.